Analisis Pertumbuhan Ekonomi dan Pengangguran di ASEAN-5 tahun 2006-2019 dengan Regresi Data Panel - Nur Afni Eka Sapitri; Atik Maratis Suhartini (Politeknik Statistika STIS, 2022)
The Association of Southeast Asian Nations was founded with the aim of being a shelter for countries in Southeast Asian to build progress and achieve prosperity. The high unemployment rate is still one of the main macroeconomic problems, including in the ASEAN-5 region (Indonesia, Malaysia, Philippines, Thailand, and Singapore) which are the founders of ASEAN. Economic growth in ASEAN countries is reported to be high for the next few years (DHL, 2020). An increase in output will require labor so this is expected to affect the unemployment rate. The purpose of this study was to analyzethe relationship between changes in the unemployment rate and economic growth by using panel data regression method. The data used is data on changes in unemployment rate and economic growth in 2006-2019 in ASEAN-5. The result of the analysis show that economic growth has a negative effect on changes in the unemployment rate. Therefore, the potential for high economic growth must be realized by promoting a labor-intensive economic sector sothat the problem of unemployment can be overcome.